Impact Of Accountability, Transferance, And Public Participation To The Work Of The Government Of The City Of Bengkulu - Della Rizka Maharani; Baihaqi Baihaqi (UNIVED Press, 2025)
This study investigates the impact of accountability, transparency, and public participation on the performance of the local government in Bengkulu City, Indonesia. Utilizing a quantitative research approach, data were collected from a sample of 50 respondents through questionnaires. The analysis included various statistical tests, such as validity and reliability assessments, normality tests, multicollinearity tests, and heteroscedasticity tests, confirming the robustness of the findings. The results reveal that all three independent variables significantly influence government performance, with accountability demonstrating the highest positive effect (p-value = 0.00), followed by transparency (p-value = 0.001) and public participation (p-value = 0.000). These findings underscore the critical role of accountability, transparency, and public participation in enhancing local government effectiveness and efficiency, ultimately aligning public expectations with government performance. The study contributes to the understanding of local governance dynamics in Indonesia and highlights the necessity for improved accountability and public engagement in decision-making processes.